The influence of social factors on help‐seeking for people with lung cancer. (4th June 2013) - Chatwin, J.; Sanders, C.
Abstract : While there has been no clear consensus on the potential for earlier diagnosis of lung cancer, recent research has suggested that the time between symptom onset and consultation can be long enough to plausibly affect prognosis. In this article, we present a review of the literature concerning help‐seeking delays in lung cancer presentation, and more specifically, the role and influence that social factors may play in determining when and how people decide to seek medical help. We also consider how these factors contribute to patients' understanding of symptoms and illness indicators. We suggest that while there is research highlighting the importance of psychosocial influences on the general help‐seeking behaviour of people with concerns about cancer, existing studies are mainly retrospective, and very little work has focused on identifying triggers and barriers specific to lung cancer. Further, we propose that while there have been a number of recent initiatives to raise awareness of the early signs of lung cancer, aimed at both patients and health professionals, little information provision has been targeted specifically at the formal and informal network level. This may be a useful avenue to pursue in future initiatives.